Managers' research education, the use of FX derivatives and corporate speculation - Oliver Entrop; Matthias F. Merkel (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2018)
In contrast to the U.S., many executive managers of continental European firms have a PhD. In this paper we analyze if a research-oriented background in the form of a PhD is linked to the corporate decision-making of CFOs in the use of foreign exchange (FX) derivatives in Germany. After controlling for fundamental firm characteristics, compensation schemes and personal characteristics of managers, we find some evidence that CFOs with a PhD in a business-related area tend to use FX derivatives less, while CFOs with a general business education do so more. Analyzing their behavior with regard to speculation, we find strong evidence that CFOs with a PhD speculate less on the FX market compared to CFOs with another (business) education. A possible reason may be that a research-oriented education is more associated with critical awareness and long-term orientation in corporate decision-making.
Keywords: G30; G32; F31; 650; FX Derivatives; Risk Management; Speculation; Behavioral Corporate Finance; PhD; Doctorate